Effect of Chop Length and Level of Molasses on Chemical Composition of Yellow Corn Stover Silage (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
This factorial study was carried out from 15/10/2020 to 31/6/2021 to investigate the effect of chop length (CL) and level of molasses (M) added at ensiling on chemical composition of yellow corn stover including leaves and stems. Those materials were chopped into 4 lengths, 5, 10, 15 and 20 mm and molasses was added as a source of soluble carbohydrates at 3 levels, 6, 8 and 10% of dry matter (DM). Urea was added to all samples at 2% to enhance nitrogen content. Samples of ensiled materials were packed in double plastic bags and preserved for 60 days.Results revealed that there was a significant (P˂0.01) increase in DM content with increasing CL and level of M, and a significant (P˂0.05) increase in crude protein (CP) content with increasing level of M. Ether extract content was significantly (P˂0.05) decreased with increasing CL but (P˂0.01) increased with increasing level of M. Regarding cell wall components, neutral and acid detergent fibers (NDF, ADF) and cellulose contents were significantly (P˂0.01) decreased in silage samples prepared at fine CL. Lower (P˂0.01) NDF and cellulose contents were associated with those prepared with addition of M at 10%. In general, it was concluded that better results were achieved when samples of yellow corn stover silages including leaves and stems were prepared at 5 mm of chop length and addition of molasses at 10%.